2021
DOI: 10.21037/apm-21-2469
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the effect of total parenteral nutrition and enteral nutrition on the prognosis of patients with acute pancreatitis

Abstract: Background: Nutritional support is very important in the treatment of severe acute pancreatitis, this study aimed to investigate the effect of total parenteral nutrition (TPN) and enteral nutrition (TEN) on the prognosis of patients with acute pancreatitis. Methods:The databases of PubMed, Embase, Cochrane Library, and Ovid were searched using the keywords acute pancreatitis, enteral nutrition, and parenteral nutrition to obtain the reports of randomized controlled trials (RCTs) published after 2000. After scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 22 publications
0
7
0
2
Order By: Relevance
“…Given these data, both the American Gastroenterological Association and ESPEN recommend that EN should be preferred to PN in patients with AP and an intolerance of oral feeding [ 114 , 127 ]. A more recent study has also explored this topic and reached the same conclusions [ 128 ]. PN is therefore only recommended in patients with AP who do not tolerate EN or who are unable to tolerate targeted nutritional requirements, or if contraindications for EN exist.…”
Section: Disease-specific Pnmentioning
confidence: 59%
“…Given these data, both the American Gastroenterological Association and ESPEN recommend that EN should be preferred to PN in patients with AP and an intolerance of oral feeding [ 114 , 127 ]. A more recent study has also explored this topic and reached the same conclusions [ 128 ]. PN is therefore only recommended in patients with AP who do not tolerate EN or who are unable to tolerate targeted nutritional requirements, or if contraindications for EN exist.…”
Section: Disease-specific Pnmentioning
confidence: 59%
“…In patients unable to tolerate ON, EN is preferred to PN and should be started early, within 24-72 h of admission according to energy requirements calculated through simplistic formulas (25-30 kcal/kg/day), published predictive equations, or indirect calorimetry [20,21]. Numerous studies have demonstrated that early initiation of EN in patients with AP is associated with significantly improved outcomes compared to PN [21][22][23].…”
Section: Nutritional Therapy In Acute Pancreatitismentioning
confidence: 99%
“…For example, the International Association of Pancreatology guideline in 2013 emphasized the significance of enteral feeding via NG or NJ over TPN in predicted severe AP [2], a recommendation consistent with subsequent guidelines [3,4]. Additional investigation is justified to determine the most effective nutritional strategies, considering the insufficiency and inconsistencies present in prior evidence, even with existing syntheses addressing this topic [5][6][7][8][9][10][11][12][13][14][15]. For instance, several studies lack differentiation between NG and NJ feeding [8,9,11,13,14], and some others do not take the timing of initiation into consideration [5,6,10,12,15].…”
Section: Introductionmentioning
confidence: 99%
“…Additional investigation is justified to determine the most effective nutritional strategies, considering the insufficiency and inconsistencies present in prior evidence, even with existing syntheses addressing this topic [5][6][7][8][9][10][11][12][13][14][15]. For instance, several studies lack differentiation between NG and NJ feeding [8,9,11,13,14], and some others do not take the timing of initiation into consideration [5,6,10,12,15]. Despite some syntheses suggesting the advantages of enteral feeding over TPN, recent evidence from American Gastroenterological Association indicates that enteral feeding does not significantly reduce the risk of mortality in comparison to TPN for patients with AP [12].…”
Section: Introductionmentioning
confidence: 99%